1972
DOI: 10.1128/aem.23.3.476-480.1972
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus Concentration on Cellulose Membranes

Abstract: Cellulose nitrate membranes were used as one of the adsorbents in concentrating viruses from water. For adsorption to occur, salts were required. With increase in valency of salt, less salt was necessary for enhanced virus adsorption to membranes. Trivalent salts were more effective because they could be used at only 1% the concentration required for divalent salts. Thus, 0.5 mm AlCl3 was as effective as 50 mm MgCl2. For testing 500 gal of water, only 0.24 kg of AlCl3 was required in contrast to 20 kg of MgCl2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
71
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 3 publications
3
71
0
Order By: Relevance
“…The modified procedures used for virus concen- a Based upon assay of the stock poliovirus added to 100 gallons of tapwater. tration has advantages over the previously described procedure (5,8) because the elimination of clarifying filters makes it less expensive, and the elimination of salt addition makes it operationally easier. When tested with small quantities of virus in 100-gallon volumes of tapwater, this modified unit was capable of concentrating the viruses nearly 40,000-fold with an average recovery efficiency of 77%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified procedures used for virus concen- a Based upon assay of the stock poliovirus added to 100 gallons of tapwater. tration has advantages over the previously described procedure (5,8) because the elimination of clarifying filters makes it less expensive, and the elimination of salt addition makes it operationally easier. When tested with small quantities of virus in 100-gallon volumes of tapwater, this modified unit was capable of concentrating the viruses nearly 40,000-fold with an average recovery efficiency of 77%.…”
Section: Discussionmentioning
confidence: 99%
“…These results were attributed to the fact that, in the presence of excess hydrogen ions, interfering organic compounds were not able to compete for membrane surface sites required by the virus. Recently, we showed that the use of salts for concentrating viruses from water in the field could be made logistically practical by the use of AlClI, a trivalent cation salt which required 100to 200-fold less salt concentration than divalent cation salts for virus attachment to membranes or textile filters (5). Studies with insoluble polyelectrolytes revealed that salts interfered with virus adsorption at increased hydrogen ion levels (6,11).…”
mentioning
confidence: 99%
“…[ Na ? ) (Wallis et al 1972). Acidification of the viral suspension also improved virus adsorption efficiency, even in the absence of exogenously added salts (Sobsey et al 1973).…”
Section: Electronegative Filtersmentioning
confidence: 96%
“…In the last decade considerable anxiety has been caused by contamination of potable waters by animal viruses and this has led to the development of methods for detecting small numbers of viruses in large volumes of drinking water. With few exceptions these methods have been specifically designed to detect acid-resistant enteroviruses, usually poliovirus, and generally use adsorption to various filters at pH 3-0-3-5 followed by elution of the viruses in a small volume of buffer-pH 10-5-1 1.5 (Wallis, Henderson & Melnick 1972;Sobsey et al 1973; Hill et al 1974; Jakubowski et al 1974;Jakubowski et al 1975;Farrah et al 1976; Hill et al 1976; Katzenelson et al 1976; Farrah et a2. 19776).…”
mentioning
confidence: 99%